3(x-3)+3x=4=-53

Simple and best practice solution for 3(x-3)+3x=4=-53 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(x-3)+3x=4=-53 equation:



3(x-3)+3x=4=-53
We move all terms to the left:
3(x-3)+3x-(4)=0
We add all the numbers together, and all the variables
3x+3(x-3)-4=0
We multiply parentheses
3x+3x-9-4=0
We add all the numbers together, and all the variables
6x-13=0
We move all terms containing x to the left, all other terms to the right
6x=13
x=13/6
x=2+1/6

See similar equations:

| 9+4x=40 | | 2v+3(8-v)=40 | | -7k+2=3k+9 | | 7−7(x+5)−8x=8-8 | | 7−7(x+5)−8x=8−8 | | 21x=14x+70 | | 7-7x-35-8x=0 | | 24m=8/10 | | 3x+4=4×+3 | | 8x+2+14x-76=180 | | 3x(7/3)=7 | | 8w=141 | | 5+2x=-3x+50 | | -1v=8 | | 0.55x+0.4x=x-3.5 | | N=-6x5 | | 4x-x-9=0 | | 3x-2+7x=-32 | | -1v=40 | | 6d-3=-2d-9 | | 7x/8=20 | | 9x+7=9x-25 | | 6-2p=p/9 | | 3x=3×+4 | | X-23l=141 | | -502.096=-815.425+t | | -8v+5(v-7)=-23 | | 18/20=x/100 | | 2(x+5)+4x=36 | | -5x+3x+1=13 | | 5w+10w-18=12 | | -19=-10+6r+13r+10r^2 |

Equations solver categories